College Algebra Applied to Arts and Business - Masajo, Gregorio S. (Quezon City : All-Nations Publishing Co., Inc., 1994)
The aims is to capitalize on the curiosity of the students desire and interest to further learn on how the numbers, its operation and expression, relation, function, and their graphs, absolute value, equation and linear inequalities, application, radicals and exponents, systems of polynomials and linear and quadratic equations and their application to be applied to arts and business.
Module 1. Algebra and four fundamentals operations -- Module 2. Special product and factoring -- Module 3. Fractions, exponents, radical and functions -- Module 4. System of linear equations, ratio and proportions -- Module 5. Worded problems, mathematics of investments -- Module 6. permutations, combination and probability.
Includes indexes.
Keywords: ALGEBRA -- ARTS AND BUSINESS